Cytological Evaluation of Palpable Non-Neoplastic Breast Lesions among Women attended from Rural Community of Bangladesh: A Retrospective Cross-Sectional Study - Rahman, Kazi Md. Shahidur; Hasan, ASM Mahmud; Nahar, Nazmun; Iqbal, Mohammad; Yusuf, Md. Abdullah; Rahman, Mashrufa (Journal of Monno Medical College, 2024)
Background: Non-neoplastic palpable breast disease is one of the most common disorders from which women suffer throughout the world. The use of fine-needle aspiration cytology (FNAC) method has proven to be quick, simple and cost-effective with minimum risk of complications in the evaluation of breast lumps. Objective: This study was planned to find out the common causes of various types of non-neoplastic breast lesions of female at different ages through fine needle aspiration cytology. Methodology: The retrospective cross-sectional study was carried out in the Department of Pathology at Monno Medical College& Hospital, Manikganj, Bangladesh. It lasted 2 years 6 months from July 1, 2019 to December 31, 2021. This study examined all breast lumps found in female patients. For data analysis, the patient's age and FNAC report were recorded. Aspirates were done using 5ml/10ml syringe and 23-gauge needle. Smears were stained with Papanicolaou stain. Results: The study included total 349 female patients with breast lesion. Among these, non-neoplastic lesions were 183(52.44%) cases and neoplastic lesions were 166(47.56%) cases. Among the lesions, 105(30.08%) cases were in fibrocystic changes; 28(8.02%) cases were in non-suppurative mastitis; 24(6.87%) cases were in suppurative mastitis (abscess), 14(4.01%) cases were in granulomatous mastitis. About 45(42.88%) cases of Fibrocystic changes, 13(44.84%) cases of non-suppurative mastitis and 9(37.5%) cases of Suppurative mastitis (abscess) were in the age group 21 to 30 years, 21 to 30 years and 41 to 50 years respectively. Conclusion: Fibrocystic changes are the commonest lesion in this study. Journal of Monno Medical College June, 2024; 10 (1):07-12